Public - private 'partnerships' in health - a global call to action - Nishtar Sania (BMC, 2004)
Abstract The need for public-private partnerships arose against the backdrop of inadequacies on the part of the public sector to provide public good on their own, in an efficient and effective manner, owing to lack of resources and management issues. These considerations led to the evolution of a range of interface arrangements that brought together organizations with the mandate to offer public good on one hand, and those that could facilitate this goal though the provision of resources, technical expertise or outreach, on the other. The former category includes of governments and intergovernmental agencies and the latter, the non-profit and for-profit private sector. Though such partnerships create a powerful mechanism for addressing difficult problems by leveraging on the strengths of different partners, they also package complex ethical and process-related challenges. The complex transnational nature of some of these partnership arrangements necessitates that they be guided by a set of global principles and norms. Participation of international agencies warrants that they be set within a comprehensive policy and operational framework within the organizational mandate and involvement of countries requires legislative authorization, within the framework of which, procedural and process related guidelines need to be developed. This paper outlines key ethical and procedural issues inherent to different types of public-private arrangements and issues a Global Call to Action.